The effects of elective abdominal surgery on protein turnover: A meta-analysis of stable isotope techniques to investigate postoperative catabolism. Issue 3 (March 2022) - Jaconelli, Matthew; Greenhaff, Paul L.; Atherton, Philip J.; Lobo, Dileep N.; Brook, Matthew S.
Summary: Background & aims: Elective surgery induces skeletal muscle wasting driven by an imbalance between muscle protein synthesis and breakdown. From examination of diverse stable isotope tracer techniques, the dynamic processes driving this imbalance are unclear. This meta-analysis aimed to elucidate the mechanistic driver(s) of postoperative protein catabolism through stable isotope assessment of protein turnover before and after abdominal surgery. Methods: Meta-analysis was performed of randomized controlled trials and cohort studies in patients undergoing elective abdominal surgery that contained measurements of whole-body or skeletal muscle protein turnover using stable isotope tracer methodologies pre- and postoperatively. Postoperative changes in protein synthesis and breakdown were assessed through subgroup analysis of tracer methodology and perioperative care. Results: Surgery elicited no overall change in protein synthesis [standardized mean difference (SMD) −0.47, 95% confidence interval (CI): −1.32, 0.39, p = 0.25]. However, subgroup analysis revealed significant suppressions via direct-incorporation methodology [SMD -1.53, 95%CI: −2.89, −0.17, p = 0.03] within skeletal muscle. Changes of this nature were not present among arterio-venous [SMD 0.61, 95%CI: −1.48, 2.70, p = 0.58] or end-product [SMD -0.09, 95%CI: −0.81, 0.64, p = 0.82] whole-body measures. Surgery resulted in no overall change in protein breakdown [SMD 0.63, 95%CI: −0.06, 1.32, p = 0.07]. Yet, separation by tracer methodology illustrated significant increases in urinary end-products (urea/ammonia) [SMD 0.70, 95%CI: 0.38, 1.02, p < 0.001] that were not present among arterio-venous measures [SMD 0.67, 95%CI: −1.05, 2.38, p = 0.45]. Conclusions: Elective abdominal surgery elicits suppressions in skeletal muscle protein synthesis that are not reflected on a whole-body level. Lack of uniform changes across whole-body tracer techniques are likely due to contribution from tissues other than skeletal muscle.